Investigation of different piezoelectric ceramics for utilization in piezoelectric EMI filters - Hubert, Florian; Dorsch, Philipp; Dürbaum, Thomas; Rupitsch, Stefan (PCIM Europe Conference Proceedings, 2020)
Increasing switching frequencies and miniaturization of switched-mode power supplies set strict requirements on the design of electromagnetic interference filters. Piezoelectric interference-suppression components are a promising new approach to improve the performance of electromagnetic interference filters. Moreover, they have the potential to reduce size, weight and cost of switched mode power supplies. However, the influence of the piezoelectric ceramic material on the filter performance has not been studied so far. As our measurement results reveal, by an appropriate choice of the ceramic material, the filter performance of a piezoelectric interference-suppression component can be improved by 40 dB in comparison to a regular Y-capacitor.
CRIS-Team Scopus Importer:2020-08-28